Bibliometric analysis of microRNAs and Parkinson’s disease from 2014 to 2023 - Chen, Lingshan; Chen, Jianfei; Weng, Wei; Wu, Min; Zhou, Xueping; Yan, Pingkang (Frontiers in Neurology, 2024)
Background Parkinson’s disease (PD) is a neurodegenerative disorder characterized by the degeneration of dopaminergic neurons. Recent research has emphasized a significant correlation between microRNAs (miRNAs) and PD. To identify key research areas, provide a comprehensive overview of current research in various fields, and propose potential directions for future studies, a bibliometric analysis was conducted on the involvement of miRNAs in Parkinson’s disease from 2014 to 2023. Methods Relevant literature records were collected from the Web of Science Core Collection on February 29, 2024. Subsequently, the data underwent analysis using the Bibliometrix R package and VOSviewer (version 1.6.19). Results The annual scientific publications on miRNAs and Parkinson’s disease demonstrated an increasing trend, with an annual growth rate of 12.67%. China, the United States, and India emerged as the top three most productive countries/regions. The University of Barcelona had the highest annual publications, followed by Central South University and the Helmholtz Association. The INTERNATIONAL JOURNAL OF MOLECULAR SCIENCES held the top position in terms of H-index and total citations, reflecting its extensive influence and prolific publication output. Kim, J., Junn, E., Hébert, S.S., and Doxakis, E. were the most frequently co-cited authors in the field. Based on the analysis of keywords, the most frequently occurring terms included “alpha-synuclein,” “neurodegenerative disease,” “exosome,” “neuroinflammation,” “oxidative stress,” “autophagy,” and “amyotrophic lateral sclerosis,” which have emerged as prominent research topics. Concurrently, there has been notable interest in topics such as “ceRNA,” “lncRNAs,” “mitochondrial dysfunction,” and “circular RNA.” Conclusion This study focused on identifying emerging trends and critical research topics in the bibliometric analysis of microRNAs related to Parkinson’s disease. These findings highlight the diverse research landscape and evolving trend of miRNA-related research in PD. The field of miRNA research in Parkinson’s disease is actively exploring the underlying mechanisms of miRNA function, identifying potential diagnostic markers, and developing innovative therapeutic strategies. The results of our study offer significant contributions to researchers’ ability to track contemporary developments and guide the trajectory of future research in this domain.